Physiological responses of two halophytic grass species under drought stress environment - Siddiqui, Zamin Shaheed; Shahid, Huda; Cho, Jung-Il; Park, Sung-Han; Ryu, Tae-Hun; Park, Soo-Chul (Acta Botanica Croatica, 2016)
The physiological responses of two halophytic grass species, Halopyrum mucronatum (L.) Staph. and Cenchrus ciliaris (L.), under drought stress were evaluated. Biomass accumulation, relative water content, free proline, H2O2 content, stomatal conductance, photosynthetic performance and quantum yield (Fv/Fm ratio) were studied. Under drought conditions, these halophytic plants expressed differential responses to water defi cit. Stomatal conductance and free proline content were higher in H. mucronatum than in C. ciliaris, while H2O2 content in H. mucronatum was substantially lower than in C. ciliaris. Performance index showed considerable sensitivity to a water deficit condition, more so in C. ciliaris than in H. mucronatum. Results were discussed in relation to comparative physiological performance and antioxidant enzymes activity of both halophytic grasses under drought stress.